Forage Yield and Nutritional Characteristics of Cultivated Fodders as Affected by Agronomic Interventions: A Review - Kumar, Rakesh; Kumar, Dinesh; Datt, Chandra; Makarana, Govind; Yadav, MR; ., Birbal (Indian Journal of Animal Nutrition, 2018)
The human population is growing rapidly which increases pressure on livestock to meet the milk demand. For the higher productivity of livestock, it is essential to provide green fodder to the livestock. The poor quality green forage not only reduces milk productivity but also affects the animal health. The qualitative green forage plays a key role in economical milk production. Forage quality mainly depends on its genetically trait; however, it can be improved by various agronomic practices viz., tillage operation, nutrient management, sowing time, seed rate, intercropping system, water and weed management, stage of harvesting, etc. The green biomass yield is significantly influenced by tillage operations; however, quality remained statistically unaffected. The right source and dose of nutrient is important for the production of good quality fodder. Addition of nitrogen to soil increased the fodder yield as well as protein content. Delayed sowing generally increase the crude protein and fiber content but decrease the crude fat. Crop density affects positively to forage yield and crude fiber; however, crude protein was negatively associated with plant density. Introducing legumes intercrops in cereal fodder improves the fodder quality as well as quantity. Forage yield follows a decreasing trend by enhancing the water scarcity; however, optimum irrigation and good quality water improves the fodder quality. Delay in harvesting time has bad impact on forage quality as it increase crude fiber content and decrease crude protein, crude fat and ash content (%). An effort is therefore, made in this review paper to collect the information of research conducted on effect of various agronomic practices on fodder quality from different part of India and abroad.